1999
DOI: 10.1007/s007840050077
|View full text |Cite
|
Sign up to set email alerts
|

Cytocompatibility of periodontal dressing materials in fibroblast and primary human osteoblast-like cultures

Abstract: Purpose of this investigation was to determine the cytocompatibility of various periodontal dressing materials by means of human primary gingival fibroblasts (HGF), human osteoblast-like cells (HObl) derived from the alveolar bone, and permanent 3T3 mouse fibroblasts (3T3). Cell culture medium extracts (time periods of extraction: day 1 and between day 2 and day 8 after setting) as well as solid specimens of the following materials were investigated: Coe-pak, Voco pac, Peripac, and Barricaid. Responses of cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…After 24-h incubation total cell lysis was observed. Another Peripac treatment on 3T3 mouse fibroblasts resulted in no viable cells after 24 h as reported by Alpar et al (1999). In our study Barricaid dressing showed the lowest inhibitory effect on cell proliferation (growth rate was reduced to 83.3 ± 9% of control after 48 h) and cell survival (SF = 0.41 ± 0.09) with fully cured material.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…After 24-h incubation total cell lysis was observed. Another Peripac treatment on 3T3 mouse fibroblasts resulted in no viable cells after 24 h as reported by Alpar et al (1999). In our study Barricaid dressing showed the lowest inhibitory effect on cell proliferation (growth rate was reduced to 83.3 ± 9% of control after 48 h) and cell survival (SF = 0.41 ± 0.09) with fully cured material.…”
Section: Discussionsupporting
confidence: 71%
“…In our study Barricaid dressing showed the lowest inhibitory effect on cell proliferation (growth rate was reduced to 83.3 ± 9% of control after 48 h) and cell survival (SF = 0.41 ± 0.09) with fully cured material. Gilbert et al (1994) and Alpar et al (1999) also found no cytotoxic alterations on fibroblasts and HeLa cells with fully cured dressing. In contrast, direct contact of uncured material caused growth inhibition and cell death.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Eugenol is generally cytotoxic at high concentrations and has an adverse effect on fibroblasts and osteoblast-like cells. [19][20][21] Thus at high concentrations it produces necrosis and reduced healing. This effect is dose related and will potentially affect all patients.…”
Section: Discussionmentioning
confidence: 99%